Visual Motifs and Symbolic Characteristics in Batak Toba Culture: A Case Study of Contemporary Kain Ulos Textile Design in Medan, Indonesia - Thio Erika Stephanie; Nurul Hanim Romainoor; Mohammad Khizal Bin Mohamed Saat (Jurnal Locus Penelitian dan Pengabdian, 2026)
This study investigates how design functions as a strategic medium to express and preserve the visual motifs of Batak Toba, particularly in ulos cloth textiles, and their integration into contemporary design practices in Medan, Indonesia. As a multicultural urban center with significant Batak Toba influences, Medan provides a dynamic socio-cultural context in which to examine how local designers interpret and adapt these motifs in modern design. This study aims to analyze the adaptation of Batak Toba ulos motifs in contemporary design and to explore the potential for cultural dilution and misrepresentation arising from the simplification of traditional forms. Using a qualitative case study approach, this study analyzed six types of ulos through Feldman's four-stage analysis method and Roland Barthes' semiotic interpretation framework. Primary data were collected through photographic documentation of ulos fabrics in Medan, while secondary data were drawn from literature related to Batak Toba culture, textile traditions, and visual semiotics. The findings indicate that although many motifs retain their visual identities, contemporary adaptations frequently simplify forms and detach them from their ritual and cosmological meanings, thereby risking cultural dilution and misrepresentation. This research proposes a visual-semiotic framework to support designers, academics, and cultural practitioners in applying ulos motifs responsibly within the context of modern design. It further emphasizes the importance of cultural literacy, semiotic understanding, and ethical considerations in preserving indigenous visual languages while allowing for the meaningful evolution of design.